THE EFFECT OF POW+TREE STRATEGY ON STUDENTS’ ABILITY IN WRITING HORTATORY EXPOSITION TEXT - Permadi Pasaribu and Isli Iriani Indiah Pane (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study deals with the effect of POW+TREE Strategy on students’ ability inwriting hortatory exposition text.. The problem of the study is to find out whetherPOW+TREE Strategy significantly affects students’ ability in writing hortatoryexposition text or not. This study was conducted by using experimental design.The population of the study was the students of eleventh grade of SMA Methodist8 Medan in the academic year 2015/2016, there were 3 parallel classes of gradeXI. There were two classes selected to be sample. The Experimental group (XIIPA-2) was taught by applying POW+TREE Strategy, while the Control group(XI IPA-3) was taught by applying conventional strategy. The data of the studywas obtained from the students’ scores of writing test. There were two kinds oftest used in this study. They were pre-test and post-test. The data were analyzedby applying t-test formula. After analyzing the data, the result of the study showedthat t-observed (2.338) was higher than t-table (1.994) (t-observed > t-table) at thelevel of significance of p=0.05 and the degree of freedom (df) = 68. It can beconcluded that applying POW+TREE strategy significantly affects students’ability in writing hortatory exposition text, or in other words, the null hypothesisis rejected , therefore the alternative hypothesis is accepted.